The Study on the Graphene and its Health Effect - M. K. Awodele; O. Adedokun; I. T. Bello; Olusola Akinrinola (Research Trends and Challenges in Physical Science Vol. 5, 2021)
The objective is to study the health implication of using graphene which may be either good or bad. This study will review of risk-related information on graphene with the purpose of outlining potential environmental and health risks. It is a guide to future risk-related research on graphene. The study will be based on the emissions, environmental fate, and toxicity of graphene. It shows that graphene could exert a considerable toxicity, emission of graphene from electronic devices and composites are possible in the future. It is known that graphene is both persistent and hydrophobic. Although these results indicate that graphene may cause adverse environmental and health effects, and that there are many risk-related knowledges gaps to be filled with the environment. Graphene can bind the cell surface and cause physical and chemical damage to the cell membrane. It is known that graphene may interact with protein and nucleic acids, altering their structure and function on the other hand, graphene may regenerate reactive oxygen species (ROS) which can also cause disruption of membrane, lipids, proteins and nucleic acids. The toxicity of graphene should be further studied.